The 4th International Electronic Conference on Atmospheric Sciences 2021
DOI: 10.3390/ecas2021-10698
|View full text |Cite
|
Sign up to set email alerts
|

Source Apportionment of Atmospheric Deposition Species in an Agricultural Brazilian Region Using Positive Matrix Factorization

Abstract: We investigated the influence of natural and anthropogenic sources on bulk atmospheric deposition chemistry, from November 2017 until October 2019, in a Brazilian agricultural area. The pH mean value was 5.99 (5.52–8.46) and most deposition samples (~98%) were alkaline (pH > 5.60). We identified Ca2+ as the predominant species, accounting for 33% of the total ionic species distribution and the main precursor of atmospheric acidity neutralization (Neutralization Factor = 6.63). PMF analysis resulted in four … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“…Excessive anthropogenic activities such as combustion processes, agriculture, industry or traffic, as well as natural processes such as volcanic eruptions, events of open fire or dust storms are nowadays considered to be the main sources of different pollutants in air [1]. Once in the atmosphere, these pollutants are subjected to various chemical and physical reactions, which change their composition, shape and properties and then, finally, by the process of atmospheric cleaning are transported from the air to the ground as atmospheric deposition (AD) [2,3]. Some studies in southern and eastern European countries have shown that AD occurs mainly as dry deposition, while wet deposition is more frequent in northern and western European countries [4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Excessive anthropogenic activities such as combustion processes, agriculture, industry or traffic, as well as natural processes such as volcanic eruptions, events of open fire or dust storms are nowadays considered to be the main sources of different pollutants in air [1]. Once in the atmosphere, these pollutants are subjected to various chemical and physical reactions, which change their composition, shape and properties and then, finally, by the process of atmospheric cleaning are transported from the air to the ground as atmospheric deposition (AD) [2,3]. Some studies in southern and eastern European countries have shown that AD occurs mainly as dry deposition, while wet deposition is more frequent in northern and western European countries [4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%